The Behaviour of the Unconfined Compressive Strength of the SiCC Mortar Improved Clays at Optimum-Wet Moisture Content - Agus Setyo Muntohar, D. Agrina (Kasetsart University, 2015)
Soil stabilization using chemical additives might be influenced strongly by the moulding moisture content for the compaction. In this paper, the result of a laboratory investigation on the application of the pozzolanic mortar column. The mortar was made of the sand and the binder microsilica and microcalcium mixtures from fine rice husk ash and carbide waste. The water to binder ratio was The primary objective of this paper is to study the effect of moisture content on the behaviour of the unconfined compressive strength of the clay-improved with SiCC mortar. The specimens were prepared in optimum – wet moisture content regime that range from 30% to 55%. The specimen size was 100 mm in diameter and 120 mm in height. The diameter of the SiCC column was 25.4 mm (1 in). The unconfined compression test was performed for each mixture after 1, 3, 7, 14 and 28 days of curing. In general, it can be concluded that the unconfined compressive strength decreased with increasing of soil moisture content for both specimen group. The specimen with SiCC column at soil moisture near OMC have the highest unconfined compressive strength. However, at a high soil moisture content, the strength development of the SiCC column supported soil was higher than the specimen at near OMC state. The unconfined compressive strength increased corresponding curing time for all soil moisture states. The results confirmed that the strength development of SiCC column supported soil depends on the soil moisture content surrounding column and curing time.